(untitled) (Cyberspace: Jurnal Pendidikan Teknologi Informasi, 2020)
Cloud computing is the transformation of information and communication technology from client or server-based computers. Cloud computing technology benefits users no longer need to invest heavily in software or maintenance software applications. So by developing the Cloud, there is a Cloud gaming which is a process to install a remote interactive game in the cloud and issued in the form of video to the user’s device via the internet. In this journal, we need a cloud gaming application called Skyegrid. This study aims to implement cloud-based mobile gaming cloud implementation using an open-source server (Skyegrid) to find out Resources, Service Quality and Experience Quality in this study. In this study Skyegrid is used to discuss some popular games, namely games called Rainbow Six Siege and Monster Hunter World. The result of this study is that Skyegrid’s cloud gaming mobile system is able to implement PC games that can be run on Android smartphones and reduce the use of CPU and RAM resources, and use low cost using skyegrid cloud gaming using personal computers that require greater costs.